MIDWIFERY CARE CONTINUITY OF CARE (COC) MRS. B, 39 YEARS OLD, G4 P2012, 37/38 WEEKS OF GESTATION + IUFD NOTOPURO REGIONAL GENERAL HOSPITAL, SIDOARJO - Agustini, Dwi; Makhina; Yusmayanti, Vilda (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aims to analyze the implementation of Continuity of Care (COC) midwifery care for Mrs. B, a 39-year-old woman (G4 P2012) at 37/38 weeks of gestation with Intrauterine Fetal Death (IUFD) at Notopuro Regional General Hospital, Sidoarjo. The study emphasizes holistic care addressing physical, psychological, social, and spiritual needs. Method: A descriptive case study approach was employed to provide an in-depth analysis of Mrs. B's condition. Data were collected through interviews, direct observations, and medical record reviews. The focus of care included pregnancy management, delivery, postpartum care, and psychosocial support. Results: The COC approach effectively facilitated comprehensive care for Mrs. B, integrating medical management of IUFD and psychosocial support to address emotional distress due to fetal loss and abandonment by her spouse. This care model promoted physical recovery and emotional resilience, contributing to Mrs. B's readiness for future reproductive health planning. Novelty: This study highlights the critical role of COC in managing IUFD cases by integrating continuous, patient-centered care that extends beyond physical treatment to encompass psychosocial recovery. The findings underscore the importance of personalized support systems for high-risk pregnancies to improve maternal health outcomes holistically.